Հուզագնահատողական արտահայտությունների ճանաչողական և հաղորդակցական առանձնահատկությունները - Գոհար Գրիգորյան (ՀՀ ԳԱԱ հրատ.)
Статья посвящена проблеме коммуникативных и когнитивных характеристик эмоционально–оценочных высказываний. Проблема состоит в том, что принятое в классической грамматике понятие "междометие" в некоторых теориях о частях речи представлено упрощенно, в результате чего изначально определенные как высказывания междометия потеряли свое коммуникативное значение и описываются только в когнитивном плане. Данная статья является попыткой переосмысления проблемы в рамках современных когнитивных теорий и теории коммуникации. The article comprises an analytical insight into the problem of cognitive and communicative features emotional–attitudinal expressions. The underlying problem is related with the need of “rehabilitation” of the communicative value of Interjections in some grammatical theories where they are represented as lexical units rather than communicative ones. This distorted interpretation of classical approach to interjections creates irrelevance in comparative studies. An attaempt is made to bring in clarity of definition and a revision of paradigmatic features from the perspective of contemporary cognitive and communicative theories.
Keywords: Language and Literature